Networked Innovation: The British Model of Industry-University Collaboration - Adam Karbowski (Zeszyty Naukowe KGŚ, 2009)
In the article the author analyzed phenomenon of industry-university collaboration in the United Kingdom. The nexus of twenty Engineering Doctorate centers in the Great Britain was thoroughly examined in the core part of the paper. The major benefits for business and academia, the most typical areas of research and the interesting examples of co-created inventions were discussed. Managerial implications and author's suggestions about possible enhancements of the British model were drawn in the final paragraphs. The British science policy-makers should then strive to design the appropriate system of incentives targeted towards creation of stable networks of potential users of scientists' research. Secondly, authorities should help the British Industrial PhD program to gain more recognition among doctoral students. Thirdly, clear communications and marketing strategy should be established to promote the EngD scheme to potential sponsors, business sectors and research engineers. The British companies should continue its increasing involvement in business-academia partnerships. Firms should strive to institutionalize internal culture of innovation. This concept postulates a creation of various organizational incentives which stimulate corporate openness and ability to learn.
Keywords: O32; 330; innovation; networks; Innovation; Network economics